When There Are Only Minorities: Identity and In-Group / Out-Group Orientations of Emerging Adults in Four South African Ethnocultural Groups. Issue 1 (February 2018) - Adams, Byron G.; Naudé, Luzelle; Nel, J. Alewyn; Vijver, Fons J. R. van de; Laher, Sumaya; Louw, Johann; Tadi, Florence
Intergroup relation perspectives stem from research in Western contexts with clear distinctions between the dominant and nondominant groups. In South Africa, with at least 13 different cultural groups and 11 official languages, no group is dominant in all life spheres. We examine the relationship between identity and in-/out-group orientation across Black-Zulu, Coloured (mixed racial ancestry), Indian, and White-Afrikaans emerging adults ( N = 390; 75% females, M age = 19.97 years, SD = 2.44). Results indicate that personal identity for all groups and ethnic identity for Black-Zulu, Indian, and White-Afrikaans emerging adults were important for intergroup relations. Black-Zulu, Coloured, and Indian emerging adults distinguish themselves less from others, whereas White-Afrikaans emerging adults are less open to others. Ultimately, the complexity of intergroup relations in South Africa has implications for the effective transformation interventions needed to counter experiences of threat and make group boundaries more flexible for emerging adults.